Key factors influencing students' choice of university for postgraduate studies abroad: A multicriteria decision model - Violeta Cvetkoska (Journal of Contemporary Economic and Business Issues, 2019)
The aim of the paper is to develop a multicriteria decision model for choosing a University for postgraduate studies abroad. The research has been conducted through a questionnaire distributed to the students from the fourth year of undergraduate studies at the Ss. Cyril and Methodius University in Skopje, Faculty of Economics - Skopje, in order to gain information on what is valuable for them, i.e. which factors are important for choosing a University for postgraduate studies abroad. Those factors that appear the most serve as inputs to the multicriteria decision model. Then, a group of 9 respondents made individual judgments for the importance of the criteria regarding the goal (choosing a University for postgraduate studies abroad), and by computing the geometric mean of the individual judgments, the group judgments are further acquired. The obtained results of the model are presented and discussed. This model will serve both students (for the purpose of choosing the most appropriate University for postgraduate studies abroad) and higher educational institutions (for the purpose of taking adequate next steps, i.e. making better decisions that will create value for students).
Keywords: C44; I23; I25; 330; university; postgraduate studies; students; AHP; group decision-making